Ofatumumab added to dexamethasone in patients with relapsed or refractory chronic lymphocytic leukemia: Results from a phase II study. Issue 5 (1st April 2015) - Doubek, Michael; Brychtova, Yvona; Panovska, Anna; Sebejova, Ludmila; Stehlikova, Olga; Chovancova, Jana; Malcikova, Jitka; Smardova, Jana; Plevova, Karla; Volfova, Pavlina; Trbusek, Martin; Mraz, Marek; et al.
<x xml:space="preserve">Abstract</x> The treatment of relapsed/refractory chronic lymphocytic leukemia (CLL) remains a challenging clinical issue. An important treatment option is the use of high‐dose corticosteroids. The purpose of this clinical trial was to determine the efficacy and toxicity of an ofatumumab–dexamethasone (O‐Dex) combination in relapsed or refractory CLL. The trial was an open‐label, multicenter, nonrandomized, Phase II study. The O‐Dex regimen consisted of intravenous ofatumumab (Cycle 1: 300 mg on day 1, 2, 000 mg on days 8, 15, and 22; Cycles 2–6: 1, 000 mg on days 1, 8, 15, and 22) and oral dexamethasone (40 mg on days 1–4 and 15–18; Cycles 1–6). The O‐Dex regimen was given until best response, or a maximum of six cycles. Thirty‐three patients (pts) were recruited. Twenty‐four (73%) pts completed at least three cycles of therapy. The remaining nine pts were prematurely discontinued owing to Grade 3/4 infections (seven pts), disease progression (one pt), or uncontrollable diabetes mellitus (one pt). Overall response rates/complete remissions (ORR/CR) were achieved in 22/5 pts (67/15%). The median progression‐free survival (PFS) was 10 months. In pts with p53 defects (n = 8), ORR/CR were achieved in 5/2 pts (63/25%) with a median PFS of 10.5 months. The median overall survival (OS) was 34 months. The Grades 3–5 infectious toxicity in 33% of pts represented the most frequent side effect during the treatment period. In conclusion, the O‐Dex regimen shows a relatively high ORR and CR with promising findings for PFS and OS. The study was registered at www.clinicaltrials.gov (NCT01310101). Am. J. Hematol. 90:417–421, 2015. © 2015 Wiley Periodicals, Inc.